Bianchi type- III, V, VIo and Kantowski-Sachs universes with varying Λ, G and σ2 simultaneously - Singh T.; Chaubey R. (My University, 2025)
The solution of Einstein's equation with variable Λ and G, in which Λ, G and the shear parameter σ2, all are coupled have been obtained for Bianchi type - III, V, VIo and Kantowski-Sachs (KS) universes in the quadrature form. Some physically interesting cases have been studied in detail. Some of the models isotropize for large time t.